A Jigsaw Technique as a Stimulant for Promoting Reading Comprehension among EFL High School Students - Amelia Mada; Sartin T. Miolo; Sri Agriyanti Mestari (Transbahasa, 2024)
This research explores the impact of implementing the Jigsaw technique as a cooperative learning strategy on the reading comprehension skills of 10th-grade students studying English as a Foreign Language (EFL) at SMA Negeri 1 Botumoito. The study specifically focuses on students' understanding of report texts, including their ability to identify main ideas, details, vocabulary, references, and inferences. The Jigsaw technique was chosen due to its potential to enhance cooperative learning and engagement among students. The study involved a sample of 60 students over eight weeks. Data were collected through pre-test and post-test assessments, and the results were analyzed using paired samples t-tests. The analysis indicated a statistically significant improvement in students' reading comprehension, with mean pretest scores of 45.55 rising to posttest scores of 74.00. The t-test results (t = 0.000, p < 0.05) confirmed the hypothesis that the Jigsaw technique positively influences reading comprehension skills. Despite some challenges, such as time constraints and dynamics between academically strong and weak students, the research interventions facilitated a positive learning environment and stimulated students' critical thinking and problem-solving skills. These findings suggest that the Jigsaw technique is an effective strategy for improving reading comprehension in EFL contexts. The study recommends further research to explore the long-term impacts and adaptations of the Jigsaw technique in diverse educational settings.